Functional and structural adaptations of the coronary macro- and microvasculature to regular aerobic exercise by activation of physiological, cellular, and molecular mechanisms: ESC Working Group on Coronary Pathophysiology and Microcirculation position paper. Issue 2 (6th August 2021) - Koller, Akos; Laughlin, M Harold; Cenko, Edina; de Wit, Cor; Tóth, Kálmán; Bugiardini, Raffaele; Trifunovits, Danijela; Vavlukis, Marija; Manfrini, Olivia; Lelbach, Adam; Dornyei, Gabriella; Padro, Teresa; et al.
Abstract: Regular aerobic exercise (RAEX) elicits several positive adaptations in all organs and tissues of the body, culminating in improved health and well-being. Indeed, in over half a century, many studies have shown the benefit of RAEX on cardiovascular outcome in terms of morbidity and mortality. RAEX elicits a wide range of functional and structural adaptations in the heart and its coronary circulation, all of which are to maintain optimal myocardial oxygen and nutritional supply during increased demand. Although there is no evidence suggesting that oxidative metabolism is limited by coronary blood flow (CBF) rate in the normal heart even during maximal exercise, increased CBF and capillary exchange capacities have been reported. Adaptations of coronary macro- and microvessels include outward remodelling of epicardial coronary arteries, increased coronary arteriolar size and density, and increased capillary surface area. In addition, there are adjustments in the neural and endothelial regulation of coronary macrovascular tone. Similarly, there are several adaptations at the level of microcirculation, including enhanced (such as nitric oxide mediated) smooth muscle-dependent pressure-induced myogenic constriction and upregulated endothelium-dependent/shear-stress-induced dilation, increasing the range of diameter change. Alterations in the signalling interaction between coronary vessels and cardiac metabolism have also been described. At the molecular and cellular level, ion channels are key players in the local coronary vascular adaptations to RAEX, with enhanced activation of influx of Ca 2+ contributing to the increased myogenic tone (via voltage-gated Ca 2+ channels) as well as the enhanced endothelium-dependent dilation (via TRPV4 channels). Finally, RAEX elicits a number of beneficial effects on several haemorheological variables that may further improve CBF and myocardial oxygen delivery and nutrient exchange in the microcirculation by stabilizing and extending the range and further optimizing the regulation of myocardial blood flow during exercise. These adaptations also act to prevent and/or delay the development of coronary and cardiac diseases.